Study on Efficacy of Expired and Active Forms of Various Antibiotics on Saccharomyces cerevisiae - Sridharan, T B; Sasvihalli, Radha S; Devi, N Prathyusha; S, Siddeswari; V, Salma; A S, Vickram; Rajeswari, Devi; Pathy M, Ramesh; Kumar S., Venkat (Research in Biotechnology, 2012)
Antibiotics are among the most frequently prescribed medications in modern medicines. The cell protection strategies in the organisms, development of resistance in previously susceptible microbes, the inevitable progression of microbes exposed to antibiotics to develop resistance, were the nesisities that ensures the need for continual cycles of discovery and development of new antibiotics. A large variety of antibiotics are available in the drug market today, several others being added regularly in combat with various pathogens that cause disease in humans as well as in animals. Our present study focused to investigate the change in efficacy of commonly used antibiotics such as amoxicillin, ampicillin, sparfloxacin, cefixime. We have collected antibiotics with before and after their expiry dates. A simple eukaryotic model organism Saccharomyces cerevisiae is used to study the comparative understanding of this microbe with these different antibiotics. In our investigation we found that response of Sacchromyces cerevisiae towards different antibiotics varied in its intricacies. Fresh forms of antibiotics have significantly inhibiting the growth of Saccharomyces cerevisiae as compared to expired forms. The observations revealed that expired forms of antibiotics loose their efficacy drastically.